2021
DOI: 10.1021/acsomega.0c06158
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CO2 Absorption by Amino Acid Salt Aqueous Solution Using Hybrid Soft Computing Methods

Abstract: Amino acid salt (AAs) aqueous solutions have recently exhibited a great potential in CO 2 absorption from various gas mixtures. In this work, four hybrid machine learning methods were developed to evaluate 626 CO 2 and AAs equilibrium data for different aqueous solutions of AAs (potassium sarcosinate, potassium l -asparaginate, potassium l -glutaminate, sodium l -phenylalanine, sodium glycinate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The principal part of the RBF neural network is the hidden layer, which transmits data from the input space to the hidden space with higher dimensions. 36 , 40 Each point of the hidden layer with a particular radius is located at a given space, and in each neuron, the distance between the input vector and its center is calculated. 41 Euclidean distance is used to measure the distance between centers and inputs, which is calculated from the following equation …”
Section: Methodsmentioning
confidence: 99%
“…The principal part of the RBF neural network is the hidden layer, which transmits data from the input space to the hidden space with higher dimensions. 36 , 40 Each point of the hidden layer with a particular radius is located at a given space, and in each neuron, the distance between the input vector and its center is calculated. 41 Euclidean distance is used to measure the distance between centers and inputs, which is calculated from the following equation …”
Section: Methodsmentioning
confidence: 99%
“…An optimized operation condition was obtained to be flow rate = 4.01 mol s −1 , temperature = 319.7 K, the pressure of flue gas = 103.5 kPa, reboiler pressure = 160.0 kPa, reboiler duty = 153,600 W, and condenser duty = 8600 W. It could be found that the optimal reaction temperature as obtained under a relatively complex condition did not deviate from that obtained under simple conditions. Besides, the CO 2 capture performance of a novel group of amine-based absorbents, that is, amino acid salt (AAs), were also recently explored by MLbased methods (Pakzad et al, 2020;Dashti et al, 2021a;Mehrabi et al, 2022). In these studies, the intrinsic features of amines, covering the molecular weight of AAs, hydrogen bond donor count, hydrogen bond acceptor count, rotatable bond count, and heavy atom count, were for the first time co-considered with the external influential factors.…”
Section: Frontiers In Energy Researchmentioning
confidence: 99%
“…FIGURE 12Regression plot for the absorption of CO 2 prognostication by (A) LSSVM, (B) RBF-NN, (C) PSO-ANFIS, and (D) ANFIS(Dashti et al, 2021a).…”
mentioning
confidence: 99%
“…In this absorption process, alkanolamines are the conventional solvents to absorb the gas. However, amino acid salt (AAS) solutions have recently shown that they could be potential alternatives as chemical absorbents due to remarkable chemical properties they possess such as high chemical reactivity, high stability against oxidation, and low viscosities [9]. In a chemical absorption process, the challenge is focused on the experimental methods for gas separation, which could be risky, tedious, and hard to carry out.…”
Section: Introductionmentioning
confidence: 99%